Feed the Future Bangladesh - A systems approach to better nutrition. Project profile. - International Potato Center (International Potato Center, 2019)
Despite the introduction of improved crops and production practices in Bangladesh, persistent malnutrition continues to adversely affect the health and wellbeing of its people, particularly women and children. Poor nutrition is also impeding the country’s development and economic growth. This project takes a consortium approach to strengthening the overall food system, aiming to empower a range of actors and increase their capacity to address the underlying causes of malnutrition.